(untitled) (Research, Society and Development, 2022)
Covid-19 exhibits a clinical picture that changes from asymptomatic infections to severe conditions, causing psychological and social disturbances at different levels of intensity and spread. Thus, health and government authorities in all countries affected by the pandemic began to warn and enact measures of quarantine, isolation or social distancing, which had an intense impact on the mental health of people in general. In this way, the objective of this article is to analyze the increase in the consumption of antidepressants as a result of the Covid-19 pandemic in Brazil, in view of the adverse effects that these substances can cause in the body. To this end, an integrative review was carried out in which the selection of studies was determined based on the inclusion and exclusion criteria. Five studies were identified in the Medline, LILACS, Scielo, CAPES Periodicals and Pubmed databases, which followed the eligibility criteria, being published from the year 2013. During the study, it was possible to identify the increase in mental and behavioral disorders, among them: anxiety, depression, post-traumatic stress disorder and sleep disorders in the Brazilian population, resulting from the Covid-19 pandemic. Studies are suggested to investigate new therapeutic treatment proposals to combat the mental limitations of the population, resulting from the Covid-19 pandemic. That said, it is necessary to integrate new educational practices in health, with an interdisciplinary sharing, focusing on the constitution of new public policies in mental health.